2004
DOI: 10.1111/j.1365-2958.2004.04396.x
|View full text |Cite
|
Sign up to set email alerts
|

Probing plasmid partition with centromere‐based incompatibility

Abstract: SummaryLow-copy number plasmids of bacteria rely on specific centromeres for regular partition into daughter cells. When also present on a second plasmid, the centromere can render the two plasmids incompatible, disrupting partition and causing plasmid loss. We have investigated the basis of incompatibility exerted by the F plasmid centromere, sopC , to probe the mechanism of partition. Measurements of the effects of sopC at various gene dosages on destabilization of mini-F, on repression of the sopAB operon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 61 publications
(100 reference statements)
7
67
1
Order By: Relevance
“…SopA uniformly binds the DNA carpet away from SopB-bound cargo (sopC-bead). We have previously shown that, under these conditions, SopA binding density on the DNA carpet is less than 1% of saturation (6), which is comparable to the in vivo estimate of 0.2% binding density per bacterial chromosome (19). SopB stimulates the release of SopA on and around the cargo, forming a local SopA gradient on the carpet by a reaction-diffusion process.…”
Section: Discussionmentioning
confidence: 83%
“…SopA uniformly binds the DNA carpet away from SopB-bound cargo (sopC-bead). We have previously shown that, under these conditions, SopA binding density on the DNA carpet is less than 1% of saturation (6), which is comparable to the in vivo estimate of 0.2% binding density per bacterial chromosome (19). SopB stimulates the release of SopA on and around the cargo, forming a local SopA gradient on the carpet by a reaction-diffusion process.…”
Section: Discussionmentioning
confidence: 83%
“…pJYB57 was made by inserting the sopC sequence, amplified by PCR from pDAG114 (29), into pBSKS(ϩ) using EcoRV and EcoRI restriction sites. pYAS6 is a pTYBI derivative (NEBioLabs) into which, the sopB-G324 gene, PCR amplified from pDAG170 (30), was inserted using NdeI and SapI restriction sites.…”
Section: Methodsmentioning
confidence: 99%
“…If one assumes that 1,000 SopA dimers exist inside an Escherichia coli cell with one chromosome (22), ∼0.2% of the chromosomal DNA would be bound by SopA. Also, nucleoid-associated proteins and transcription factors dynamically occupy a significant fraction of the bacterial chromosome and likely prevent SopA from forming stable higherorder complexes on the nucleoid surface.…”
mentioning
confidence: 99%